Optimization of Financial Performance: A High-Tech Project Financial Management Model for Successful Implementation - Reni Nurlaela (Jurnal Ekonomi, 2024)
In the context of the high-tech era, innovative projects have a key role in the progress of an organization. The successful implementation of high-tech projects depends not only on technical excellence, but also on efficient financial management. This article describes an optimal financial management model for such innovative projects, with the aim of achieving sustainable implementation success. High-tech projects, which often involve large financial investments, require efficient financial management to overcome potential obstacles. Complexity and rapid changes in technology and business add to the level of difficulty in managing the project's finances. High-tech project financial management models are considered a key strategy for managing project finances effectively. The discussion includes practical steps such as financial audits, preparation of initial budgets, preparation of periodic financial reports, and monitoring financial performance. Financial audits help identify financial leaks and imbalances across projects, while preliminary budgets help prioritize project tasks. The key to financial management in high-tech projects is optimizing financial performance and implementing strict monitoring strategies. Effective financial management makes project management easier to face complex challenges. This article provides in-depth insight into high-tech project financial management models, including case studies of successful implementation of Earned Value Management (EVM) models. The critical factors for successful implementation of a financial management model involve stakeholder support, effective communication, adaptation to change, project team involvement , effective risk management, technology and supporting systems, clear performance measurement, and human resource training. This article recommends a hybrid approach that combines elements of Waterfall and Agile , with an emphasis on communication, risk management, and effective performance measurement to overcome challenges in high-tech projects.